To compare the gingival melanin repigmentation after diode laser application and surgical removal - Gaurav Mahajan; Harjit Kaur; Sanjeev Jain; Navnit Kaur; Navneet Kaur Sehgal; Aditi Gautam (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the present study is to compare the gingival melanin repigmentation after diode laser application and surgical removal done by scraping with Kirkland knife. Materials and Methods: This study was a randomized split-mouth study where 10 patients presenting with unattractive, diffuse, dark brown to black gingival discoloration on the facial aspect of the maxillary gingiva were treated by diode laser application and surgical removal and followed up for 3-, 6-, and 9-month intervals. Results: The results showed a statistically significant difference in repigmentation between the groups at the interval of 3 months (P = 0.040), but the difference was statistically not significant at 6 months (P = 0.118) and 9 months (P = 0.146). On surgically treated sites, all cases showed repigmentation of the gingiva, but in laser treated, there were two individuals which did not show repigmentation of the gingiva even at the end of 9-month observation time. Conclusion: The incidence of repigmentation was slightly less in laser-treated sites as compared to surgical depigmentation although the difference was statistically significant only up to 3 months.